Precariato, università e narrazione: Le prospettive di Carbé, Inglese e Targhetta - Lapia, Roberto (Status Quaestionis, 2019)
In this article, after introducing some key concepts on the precarization of work, I propose to analyze how contemporary Italian fiction has been able to represent the frustrations of the precarious people working in academia, giving voice to the anxieties deriving from the degradation of an increasingly unstable work situation. The texts in question (by Andrea Inglese, Francesco Targhetta and Emanuela Carbé), through a highly subjective perspective, highlight the need for an in-depth reflection on the precariousness inoculated in the person as perception of the self, as well as on the testimonial role of literature.